PENGARUH INTENSITAS, KUALITAS, DAN SIKAP ATAS KOMUNIKASI ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN INVESTASI - PRADNYANI, I GUSTI AGUNG ARISTA; ATMAJA, I GUSTI PUTU WIDYA; RAHAYU, NILA; ANWAR, ADRIANDA (Ganec Swara, 2025)
Investment decisions are the process of allocating funds to various investment options with the aim of gaining profit or increasing the value of assets in the future. Students are interested in joining GI KSPM FEB Universitas Mataram because of their desire to learn more about the world of investment, financial instruments, and capital markets. Financial behavior refers to the actions or behavior of individuals in managing finances in various ways, in accordance with the Finance Behavior Theory. However, this does not happen by chance where there are other influential factors such as marketing communications which today rely more on digital, specifically the intensity of viewing or watching, the quality of what is watched, and attitudes towards electronic Word of Mouth communication. This research was conducted in the Mataram City Area and was more specifically at GI KSPM FEB Universitas Mataram. The research time was 2024. This research is an associative research with a quantitative approach using data collection methods in the form of distributing questionnaires. The statistical analysis used includes descriptive statistical tests, validity tests, reliability tests, normality tests, multicollinearity, heteroscedasticity, determination coefficient tests, F tests and t tests. Data analysis using multiple linear regression analysis. The results show that intensity has a positive effect, the quality of electronic word of mouth does not have a significant effect, and attitudes towards electronic word of mouth communication have a positive effect on investment decisions.